Managing the Politics of Reform : Overhauling the Legal Infrastructure of Public Procurement in the Philippines - Campos, J. Edgardo (Washington, DC: World Bank, 2012)
Over the past 30 years there has been considerable research on the political economy of reform. Yet despite this, little is known about strategies for managing the politics of change-moving from a bad to a better equilibrium. Part of the challenge of studying this issue stems from the difficulty of obtaining detailed, so-called "blow-by-blow" information on actual reform processes. From this type of information, one can discern and cull practical lessons on strategy, which by its very nature is about dealing with political barriers or problems as they crop up during the implementation process. This study looks at the sequence of events that ultimately led to the passage of legislation that markedly altered the rules that govern public procurement in the Philippines. The study attempts to distill operationally useful lessons for managing the politics of a reform process.